2017
DOI: 10.1016/j.ccell.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

MLL2, Not MLL1, Plays a Major Role in Sustaining MLL-Rearranged Acute Myeloid Leukemia

Abstract: Summary The MLL1 histone methyltransferase gene undergoes many distinct chromosomal rearrangements to yield poor-prognosis leukemia. The remaining wild-type allele is most commonly, but not always, retained. To what extent the wild-type allele contributes to leukemogenesis is unclear. Here we show using rigorous, independent animal models that endogenous MLL1 is dispensable for MLL-rearranged leukemia. Potential redundancy was addressed by co-deleting the closest paralog, Mll2. Surprisingly, Mll2 deletion alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 61 publications
7
78
2
1
Order By: Relevance
“…Remarkably, in both cell lines we did not detect any significant defect in cell growth, despite effective knockout of ZFP64 (Figure 6E and S5C–D). We performed ChIP-seq and RNA-seq in the human retroviral MLL-AF9/Nras G12D AML cells and confirmed the exceptional level of ZFP64 occupancy at the endogenous MLL promoter and verified the ZFP64 requirement to express endogenous MLL WT , which is dispensable in MLL fusion leukemia models (Chen et al, 2017) (Figure 6F and S5E). To further corroborate this finding, we evaluated the effect of Zfp64 knockout in a mouse leukemia model in which MLL-AF9/Nras G12D oncogenes are expressed via a retroviral LTR promoter (RN2 cells) and in a knock-in leukemia model in which MLL-AF9 is expressed from the endogenous Mll promoter (Corral et al, 1996).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Remarkably, in both cell lines we did not detect any significant defect in cell growth, despite effective knockout of ZFP64 (Figure 6E and S5C–D). We performed ChIP-seq and RNA-seq in the human retroviral MLL-AF9/Nras G12D AML cells and confirmed the exceptional level of ZFP64 occupancy at the endogenous MLL promoter and verified the ZFP64 requirement to express endogenous MLL WT , which is dispensable in MLL fusion leukemia models (Chen et al, 2017) (Figure 6F and S5E). To further corroborate this finding, we evaluated the effect of Zfp64 knockout in a mouse leukemia model in which MLL-AF9/Nras G12D oncogenes are expressed via a retroviral LTR promoter (RN2 cells) and in a knock-in leukemia model in which MLL-AF9 is expressed from the endogenous Mll promoter (Corral et al, 1996).…”
Section: Resultsmentioning
confidence: 65%
“…Both MLL fusion and MLL WT proteins are expressed in MLL -rearranged leukemia, since the MLL rearrangements is heterozygous. However, discrepancies exist in the literature regarding the essentiality of MLL WT for leukemogenesis, which may reflect different genetic targeting strategies used in these studies (Cao et al, 2014; Chen et al., 2017; Mishra et al, 2014; Thiel et al, 2010). However, recent studies have shown that MLL WT is essential to support a leukemogenic transcriptional program in the NPM1 -mutant and NUP98 -rearranged subtypes of leukemia (Kuhn et al, 2016; Xu et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in MLL-AF9-driven acute myeloid leukemia, germline MLL promotes proliferation and survival (Thiel et al 2010) and cooperates with MLL-AF9 for efficient transactivation of the HOXA9 locus (Milne et al 2010). Other studies suggest that germline MLL2 rather than MLL is essential for MLL-AF9 leukemogenesis; however, MLL contributes to leukemia cell survival through collaboration with MLL2 BCL2L11 BCL2L11 BCL2L11 BCL2L11 BCL2L11 BCL2L11 BCL2L11 CDKN1A CDKN1B CDKN2A CDKN2A CDKN2A CDKN2D TP53BP1 TP53BP1 TP53 TP53 -3 ( Chen et al 2017). Germline MLL is more active than MLL-AF4 in protecting CpGs from methylation, while MLL-AF4 is a more potent transcriptional activator (Erfurth et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…DPY30 may, however, support MLL-rearranged leukemias by regulating the activity of endogenous MLL1 and/or MLL2, which have been shown to be important in sustaining these leukemias (57,58). Moreover, we have previously shown that DPY30 regulates the activity of the MYC oncogene through two different levels: (i) DPY30 directly promotes the expression of MYC gene, as shown in MLL-rearranged leukemia cells (17), Burkitt's lymphoma, and Jurkat cells (20), and (ii) DPY30 regulates chromatin accessibility and enables efficient binding of MYC oncoprotein to many of its genomic targeting (20).…”
Section: Discussionmentioning
confidence: 99%